The Important Role of Financial Architecture Regulation Toward Fintech P2P Lending Ecosystem - Wijaya, Chandra; Nugroho, Bernardus Yuliarto; Arkanuddin, Mohammad Fahmi (School of Business, IPB University (SB-IPB), 2024)
The purpose of this research is to analyze the significant impact role of financial architecture regulation in the fintech peer-to-peer (P2P) lending ecosystem, using a quantitative approach and the SEM-Amos analysis tools. The research period was carried out around 2022, using research instruments in the form of distributing questionnaires, and the respondents were users of the P2P lending fintech mobile application spread, both as borrowers - lenders and interviews with stakeholders in the P2P lending fintech industry. The results indicated a significant impact of financial architecture regulation on the fintech P2P lending ecosystem, with an estimated value of 0.922. This finding demonstrates that financial architecture regulation plays a crucial role in establishing a strong and stable fintech P2P lending ecosystem. The provision of regulations, is one of the core functions of regulatory bodies and serves to guide and direct the future development of this industry. It is essential that regulations address key aspects such as big data analytics, automation and robotics, which serves as the basis for the development of information technology (IT),) to strengthen the fintech P2P lending ecosystem. Keywords: financial architecture regulation, Fintech P2P Lending Ecosystem, fintech industry, SEM